2019
DOI: 10.1016/j.culher.2019.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of an augmented reality application for rock art visualization in Cova dels Cavalls (Spain)

Abstract: Prehistoric rock art paintings, specifically rock-shelters exposed to environmental and anthropogenic factors, are usually faint and severely damaged, being them difficult to identify and understand by visitors. Augmented Reality (AR) supplements reality with virtual information superimposed onto the real world. This sensor-based technology in smartphones/tablets can improve the paintings experience displaying the 2D digital tracings overlapped onto the real scene (rock with faint paintings). This paper presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 55 publications
0
24
0
1
Order By: Relevance
“…Previous research concluded that visitors find AR experiences attractive and that it may favour destination choice (Puyuelo et al, 2013;Chung et al, 2015;Blanco-Pons et al, 2019). However, at this point, the users of Regaleira 4.0 displayed mixed feelings.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Previous research concluded that visitors find AR experiences attractive and that it may favour destination choice (Puyuelo et al, 2013;Chung et al, 2015;Blanco-Pons et al, 2019). However, at this point, the users of Regaleira 4.0 displayed mixed feelings.…”
Section: Discussionmentioning
confidence: 77%
“…The main features that tourists find attractive in AR experiences are the thrill of trying out an innovative experience, the visual nature of AR, and the situational nature of AR, which affords adaptation to context and personalization. All these factors reinforce the perception of AR as useful and may favour destination choice (Puyuelo, Higón, Merino, & Contero, 2013;Chung, Han & Joun, 2015;Blanco-Pons, Carrión-Ruiz, Lerma, & Villaverde, 2019). Concerning satisfaction with AR experiences of cultural heritage visits, the most important factors are technological quality, quality of content and the personalization of the experience.…”
Section: Enhancing Cultural Heritage With Armentioning
confidence: 78%
“…Nowadays, Information and Communication Technologies (ICT), coupled with the evolution of smartphones, make AR applications attractive to CH sites like museums because they can be used to show different types of content to a wider audience [83]. As such, the number of AR applications used in CH is on the increase, and future predictions suggest this will be accompanied by an exponential increase in the numbers of AR technology users [91]. Chang [26], for example, describes a study designed to identify the experience the user has with AR in an art appreciation class and concludes that employing AR is more effective compared to the use of audio guides in an art museum.…”
Section: What Advantages Disadvantages Limitations and Challenges Dmentioning
confidence: 99%
“…Another disadvantage in AR is that the tracking methodology based on markers could be intrusive in some scenarios [81]. In the same vein, it is important to consider different aspects that might affect the user's experience; for example, in [91], they mention that in their application, the virtual content takes too much time to appear in the mobile device. An article by Martinetti [114] mentions that the main factors for the lack of AR pervasiveness are technological/technical limitations (image recognition, internet connection, responsiveness), human interaction (distraction and ergonomic devices) and organizational limitations (handling AR projects, IT infrastructure and financial resources).…”
Section: What Advantages Disadvantages Limitations and Challenges Dmentioning
confidence: 99%
“…Ma et al (2018) [26] developed a smart sightseeing application system combining AR technology and a paper sightseeing map for emergency response. Blanco-Ponsa et al (2019) [27] presented an application that provides information related to cultural heritage. Makino et al (2019) [28] developed a system that visualizes spatiotemporal information in both real and virtual spaces, integrating social networking services (SNS), Web GIS, mixed reality (MR) and the original gallery system, as well as Wikitude and connecting external social media.…”
Section: Related Workmentioning
confidence: 99%